2021
DOI: 10.3389/fonc.2021.655322
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT in the Radiotherapy Treatment Planning of Locally Advanced Anal Cancer: A Monoinstitutional Experience

Abstract: AimsRadiotherapy with concurrent 5-fluorouracil/mitomycin-C based chemotherapy has been established as definitive standard therapy approach for anal cancer. Intensity Modulated Radiotherapy (IMRT) leads to a precise treatment of the tumor, allowing dose escalation on Gross Tumor Volume (GTV), with a surrounding healthy tissues sparing. Our study assessed the impact of 18-Fluorodeoxyglucose positron emission tomography (18FDG-PET/CT) on the radiotherapy contouring process and its contribution to lymphatic sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The European Organization for Research and Treatment of Cancer (EORTC) 22931 10 and Radiation Therapy Oncology Group (RTOG) 95-01 randomized clinical trial 6 demonstrated the survival benefit of concurrent chemoradiotherapy in high-risk head and neck cancer patients. This paved the way for chemoradiotherapy to become the standard treatment protocol 22 , 23 for locally advanced OPSCC patients, regardless of HPV status. However, clinical characteristics and treatment response differ between various head and neck cancer subsites 24 (e.g., oropharyngeal, laryngeal and oral cavity).…”
Section: Discussionmentioning
confidence: 99%
“…The European Organization for Research and Treatment of Cancer (EORTC) 22931 10 and Radiation Therapy Oncology Group (RTOG) 95-01 randomized clinical trial 6 demonstrated the survival benefit of concurrent chemoradiotherapy in high-risk head and neck cancer patients. This paved the way for chemoradiotherapy to become the standard treatment protocol 22 , 23 for locally advanced OPSCC patients, regardless of HPV status. However, clinical characteristics and treatment response differ between various head and neck cancer subsites 24 (e.g., oropharyngeal, laryngeal and oral cavity).…”
Section: Discussionmentioning
confidence: 99%
“…Another finding was a nonsignificant trend towards a lower RT boost volume (≤ 241.1 cm 3 vs. > 241.1 cm 3 ; P = 0.197) in patients with PET-CT planning. PET-CT may serve as a further diagnostic tool to precisely confirm the location of the PT and detect affected/unaffected lymph nodes, thus influencing staging and target volume delineation [48][49][50][51][52][53][54]. In a study by Zimmermann et al [51], upstaging and downstaging by PET-CT were reported in 13% of cases each for nodal disease, with a consequent change in treatment planning for 17% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In these 14 cases, dose escalation was performed on the FDG-PET/CT-positive nodes. According to this study, FDG-PET/CT is particularly important for the detection of inguinal LNMs [21]. We can assume due to the moderate specificity and high sensitivity and due to the major changes in treatment planning when FDG-PET/CT is used that it is indispensable for detecting and contouring LNMs in AC in the context of curative radiotherapy for dose escalation.…”
Section: Anal Canal Cancermentioning
confidence: 93%